2013
DOI: 10.1371/journal.pone.0077635
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Transmission among Immigrants and Autochthonous Populations of the Eastern Province of Saudi Arabia

Abstract: BackgroundEastern province of Saudi Arabia is an industrial zone with large immigrant population and high level of tuberculosis case notification among immigrants. The impact of immigration and current trends of tuberculosis transmission among immigrants and autochthonous population in the region had not been investigated so far using molecular tools.MethodologyDuring 2009- 2011, a total of 524 Mycobacterium tuberculosis isolates were collected from the central tuberculosis reference laboratory, representing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
5
15
1
Order By: Relevance
“…Our result matched also with that of Varghese et al [34] who reported no significant differences of drug-resistance rate between immigrants and local population in Saudi Arabia. Therefore, screening of expatriate workers and illegal immigrants into the Kingdom might help to control spread of TB infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result matched also with that of Varghese et al [34] who reported no significant differences of drug-resistance rate between immigrants and local population in Saudi Arabia. Therefore, screening of expatriate workers and illegal immigrants into the Kingdom might help to control spread of TB infection.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, screening of expatriate workers and illegal immigrants into the Kingdom might help to control spread of TB infection. The Ministry of Health of the KSA has implemented such a plan and its effects will be evaluated over the next few years [34].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cross-national transmission among the immigrant groups was very limited (24.2%). This study concluded that the socio-economical characteristics of the migrant group have a distinctive and detectable impact on the diversity of strain lineages and transmission dynamics of TB in the eastern province of Saudi Arabia [6].…”
Section: Transmission Dynamics Of Tb In Saudi Arabiamentioning
confidence: 79%
“…Varghese et al recently reported on the transmission of TB among the autochthonous and immigrant populations of the eastern province in Saudi Arabia, which has a large population of migrants [6].The recent transmission index in the region was 32.1%. Of particular interest was the observation that 75.8% of the strain clusters were shared between indigenous and immigrant populations, particularly immigrants from Southeast Asia (40.7%).…”
Section: Transmission Dynamics Of Tb In Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation